Optimization studies on cellulase and xylanase production by Rhizopus oryzae UC2 using raw oil palm frond leaves as substrate under solid state fermentation - Ezeilo U.R.; Wahab R.A.; Mahat N.A. (Elsevier Ltd, 2024)
Increasing energy demands call for sustainable alternative sources. Solid state fermentation (SSF) of raw oil palm frond leaves (OPFL) as the substrate to produce extracellular cellulases and xylanase by a novel Rhizopus oryzae UC2 (GenBank accession no. MF767597) was optimized. Optimum SSF conditions (30 °C, 40% moisture content, 2.0 × 108 spores/g inoculum size) yielded the maximum carboxymethyl cellulase (CMCase) (94.68 U/g), filter paperase (FPase) (25.46 U/g), β-glucosidase (145.47 U/g) and xylanase (213.99 U/g) activities, showing a broad pH range of between 6.0 and 12.0. Proteome analysis of crude enzyme cocktail revealed three β-glucosidases, as well as one endo-β-1,4-glucanase, exoglanase and endo-β-1,4-xylanase each. Activities of the enzyme complex were maximal at an acidic pH and temperature that ranged between pH 3.0–5.0 and 50–60 °C, respectively. In situ hydrolysis of OPFL released various concentrations of sugars viz. glucose (26.74 mg/g), xylose (1.44 mg/g), fructose (50.8 mg/g) and cellobiose (58.31 mg/g). Moreover, CMCase, FPase, β-glucosidase and xylanase exhibited half-lives of 5.13, 1.48, 18.81, 9.23 h when incubated at 60 °C, respectively. Thus, the desirable qualities of R. oryzae UC2 seen here supported its prospective biocatalytic role for timely and safe production of digestible carbohydrates from agro-industrial biomass for the subsequent biotransformation into biofuel. © 2019 Elsevier Ltd